Sustainability Reporting In Malaysia: Impression Management And The Influence Of Internal Resources - Wong, Chong Chie (2024)
Bursa Malaysia mandated the presentation of sustainability statements in annual reports for public listed companies in 2016. The research attempts to study companies' reactions to this requirement, focusing on their compliance and impression management levels aiming to evaluate if companies are prepared for mandatory sustainability reporting and if their transparency and authenticity are intact. This research explores the impact of resource-based theory on impression management, suggesting that companies with strong sustainability performance might not resort to impression management if they deploy sufficient resources in their sustainability operations. The study uses mixed methods to address the research questions. Firstly, content analysis is done to study the sustainability statements of the top 100 largest public listed companies in Malaysia to analyse their compliance level and impression management level. Regression analysis is then performed to test the influence of internal resources on the impression management level by using the existence of a sustainability committee, sustainability vision and mission statement, financial performance, adoption of an environmental management system, experience in voluntary sustainability reporting, and sustainability related award winning as the independent variables. Next, interviews are conducted to provide further insight into the results obtained above.